Navigational Transmaxillary Endoscopic Approach for Inferomedial Tumors - Wu, Cheng-Hsien; Ho, Yi-Yun; Liu, Tzu-Lun; Wu, Tzu-Ying; Cheng, Han-Chieh; Tsai, Chieh-Chih (Frontiers in Oncology, 2022)
Objective: Orbital tumors (OTs) encompass a heterogeneous range of histopathology and are usually variable in terms of location. For lesions close to the orbital apex, an increased risk of soft tissue sequelae and optical-nerve injury cannot be overlooked. Endoscopic approach to the orbital walls provides a minimally invasive way to remove the orbital pathologies. However, the popular transnasal endoscopic approach has narrow nasal corridor to the medioapical region of the orbit and usually additional osteotomy to gain access and the resultant medial orbital defect is difficult to repair. In this report, we propose a novel computer-assisted endoscopic protocol to excise medial OTs with immediate repair of the wall defect. Patients and Methods: A surgical approach through the maxillary sinus to the orbital floor which comprise of the endoscope and intraoperative navigation (Navigational TMEA: navigational transmaxillary endoscopic approach) was proposed. The patient’s digital images were rendering and segmentation for virtual surgical planning (VSP). The VSP was then transferred to the operating theatre by printing models and surgical navigator. A maxillary sinus window was created for surgical access. Endoscopic excision of the medial OTs was performed under navigation guidance. The orbital walls were immediate repaired with biocollagen membrane or titanium plates. Results: Two patients with medial OTs and excised with navigational TMEA were enrolled. The mean volume of the tumors was 7.3mm3. The operation time was 167.5 minutes with minimal blood loss (42.5ml). The average hospital stay was 3.5 days. All the patient experience transient midface numbness and diplopia which totally resolved in 2 months without long term complications. Conclusion: The TMEA provides a versatile surgical corridor to the inferior and medial orbit (and even to the orbital apex). With this computer-assisted workflow, one can implement virtual surgical planning, intraoperative navigation, and true-to-original orbital-wall reconstruction that shortens the duration of the procedure and hospital stay, and reduces the risk of complications.